Pengaruh Takaran Pupuk Kandang Sapi terhadap Pertumbuhan dan Hasil Jagung (Zea mays L.) yang Ditumpangsarikan dengan Kedelai (Glysine max (L.) Merril) - Wendalinus Leki; Maria Afnita Lelang; Roberto I. C. O. Taolin (Savana Cendana, 2016)
This study aims to determine the effect of cow manure dosage on growth and yield of maize that intercropped with several varieties of soybeans. The experiment was conducted in the garden of Agriculture Faculty, Timor University using Factorial Random Block Design with three replications. The first factor is the dosage of cow manure which consists of three levels ie without fertilizer, 30 t / ha, and 40 t / ha. The second factor is soybean varieties consisting of three levels namely Davros, Willis and local. The results showed no interaction effect between dosage of cow manure and soybean varieties to all parameters observed. The dose of cow manure significantly influences the soil temperature of 75 days after planting (DAP), a moisture content of 50 DAP, stem diameter 25 DAP, number of seeds per line, dry weight of 100 seeds, dry weight of seed per plot and harvest index. Soybean varieties significantly affect the number of rows per corncob, the number of seeds per line and the dry weight of seeds per plot. Cow manure 40 t / ha is better dosage and Local varietal soybean is more suitable for intercropping with maize that yields 1.0 t / ha and 0.7 t / ha soybeans.